Anticipating The Return of Foreign Terrorist Fighters: Indonesia-Australia’s Initiative on Sub-Regional Meetings on Counterterrorism - Nuri Widiastuti Veronika (Jurnal Hubungan Internasional, 2022)
Efforts to overcome the increasing security threats of terrorism, violent extremism, and Foreign Terrorist Fighters (FTFs) have encouraged policymakers in Indonesia and Australia to strengthen cooperation in the security sector. Despite the Indonesian-Australian “turbulent” history of their bilateral relationship, the two countries have initiated a high-level meeting called the Sub-Regional Meeting (SRM) on Counter-Terrorism. Starting with six participants in 2017 (Indonesia, Australia, New Zealand, Malaysia, Brunei Darussalam, and the Philippines), Indonesia-Australia’s co-leadership has attracted Myanmar, Singapore and Thailand to join the 2018 Jakarta meeting and the 2020 virtual meeting. Analyzing Indonesia and Australia’s initiative on the SRM can determine to what extent this cooperation has addressed the returning FTFs as one of the most imminent regional security threats in the Asia Pacific. This study adopted Buzan and Weaver’s regional security complex elements in explaining to what extent this regional security issue has put aside Indonesian-Australian differences and led them to the co-leadership position in anticipating the return of FTFs to Asia Pacific, prone to terrorist attacks and violent extremist beliefs. The analysis unveiled that Indonesia-Australia’s SRM initiative to anticipate the return of FTFs could, to some extent, address the elements of security complexes in the Asia Pacific subregion through the mutual co-leadership, reduce the lack of regional trust and foreign policy dilemmas, build bonded trust across all levels of government administration, and obtain the advantage of the securitization of the return of FTFs.